2018
DOI: 10.1007/s40487-018-0089-z
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukin-1 in the Pathogenesis of Cancer and its Potential as a Therapeutic Target in Clinical Practice

Abstract: Interleukin-1 (IL-1) has long been known to be a key mediator of immunity and inflammation. Its dysregulation has been implicated in recent years in tumorigenesis and tumor progression, and its upregulation is thought to be associated with many tumors. Overexpression of the IL-1 agonists IL-1a and IL-1b has been shown to promote tumor invasiveness and metastasis by inducing the expression of angiogenic genes and growth factors. IL-1 blockers such as anakinra and canakinumab are already approved and widely used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 101 publications
1
61
0
4
Order By: Relevance
“…In order to investigate potential role of soluble molecules on thrombocytosis development, we have further analyzed systemic concentrations of cytokines of interest. IL-1 is potent cytokine involved in variety of pro-inflammatory processes, but also in tumorigenesis and tumor progression 25 . Besides direct stimulating effect on tumor cell proliferation, it has also been shown that colon cancer cell-derived IL-1α may upregulate angiogenesis by modulating stromal cells within the tumor microenvironment 15 .…”
Section: Figure 4 Discussionmentioning
confidence: 99%
“…In order to investigate potential role of soluble molecules on thrombocytosis development, we have further analyzed systemic concentrations of cytokines of interest. IL-1 is potent cytokine involved in variety of pro-inflammatory processes, but also in tumorigenesis and tumor progression 25 . Besides direct stimulating effect on tumor cell proliferation, it has also been shown that colon cancer cell-derived IL-1α may upregulate angiogenesis by modulating stromal cells within the tumor microenvironment 15 .…”
Section: Figure 4 Discussionmentioning
confidence: 99%
“…It was also found that high tumour co-expression of the VEGF and IL-6 family cytokines significantly lowers the human epidermal growth factor receptor 2 (HER2) negative BC survival (11). Moreover, higher expression of pro-inflammatory IL-1β cytokine is correlated with higher BC stage and significantly worse survival (12). In addition, IL-1α acts as a pro-inflammatory molecule itself and also promotes the activity of IL-1β, resulting in an increased growth of BC cells and tumour progression (13).…”
Section: Association Of Angiogenesis and Inflammation-related Gene Fumentioning
confidence: 99%
“…As far as IL-1α SNP is concerned, Um et al (18) demonstrated that the IL-1α rs1800587 CC genotype is associated with higher transcriptional activity of the IL-1α gene. Overexpression of the IL-1α promotes tumour invasiveness and metastasis by inducing the expression of angiogenic genes and growth factors (12). A large meta-analysis performed by Xia et al (30) showed that the IL-1α rs1800587 C allele and CC genotype are associated with increased cancer risk in general.…”
Section: Pfs Mfs Os -------------------------------------------------mentioning
confidence: 99%
“…The presence of OCs leads to increased local and systemic inflammation ( Figure 2 ). Within the tumor microenvironment (TME), OC cells, infiltrating immune cells and other cells including fibroblasts, endothelial cells and adipocytes continuously secrete pro‐inflammatory cytokines, including IL‐6, TNF, IL‐1, and IL‐8 58–60 . The level of these cytokines in the serum of OC patients is associated with poorer prognosis 58–60 .…”
Section: Ovarian Cancermentioning
confidence: 99%
“…Within the tumor microenvironment (TME), OC cells, infiltrating immune cells and other cells including fibroblasts, endothelial cells and adipocytes continuously secrete pro‐inflammatory cytokines, including IL‐6, TNF, IL‐1, and IL‐8 58–60 . The level of these cytokines in the serum of OC patients is associated with poorer prognosis 58–60 . High levels of IL‐6 or TNF in ascites is associated with shorter progression‐free survival 58,60 and circulating CRP levels are associated with increased risk of ovarian cancer 61,62 …”
Section: Ovarian Cancermentioning
confidence: 99%